Quantifying Cell Proliferation Through Immunofluorescence on Whole-Mount and Cryosectioned Regenerating Caudal Fins in African Killifish - Augusto Ortega Granillo; Robert Schnittker; Wei Wang; Alejandro Sánchez Alvarado (Bio-Protocol, 2023)
The African killifish Nothobranchius furzeri is an attractive research organism for regeneration- and aging-related studies due to its remarkably short generation time and rapid aging. Dynamic changes in cell proliferation are an essential biological process involved in development, regeneration, and aging. Quantifying the dynamics of cell proliferation in these contexts facilitates the elucidation of the attendant underlying mechanisms. Whole-mount and cryosectioning sample preparation are the preferred approaches to investigate the distribution of cellular structures, cell–cell communication, and spatial gene expression within tissues. Using African killifish caudal fin regeneration as an example, we describe an efficient and detailed protocol to investigate cell proliferation dynamics in both space and time during caudal fin regeneration. The quantification of cell proliferation was achieved through high-resolution immunofluorescence of the proliferation marker Phospho-Histone H3 (H3P). We focused on the characterization of epithelial and mesenchymal proliferation in three-dimensional space at two regeneration time points. Our protocol provides a reliable tool for comparing cell proliferation under different biological contexts.Key features• Elaborates in detail the method used by Wang et al. (2020) to quantify whole-organ mitotic events during tail fin regeneration in vertebrates.• Enables proliferation analysis of millimeter-sized homeostatic and regenerating tissues.• Three-day alternative method to whole mount using cryosections.• Allows automatic quantification using ImageJ macros and R scripts.Graphical overview